Enantioselective synthesis of polyhydroxyindolizidinone and quinolizidinone derivatives from a common precursor - Saha, Nemai; Chattopadhyay, Shital K. (Beilstein Journal of Organic Chemistry, 2014)
A concise asymmetric synthetic route to two new tetrahydroxyindolizidinone and quinolizidinone derivatives has been developed from a common intermediate which featured a highly selective dihydroxylation reaction and a RCM reaction as key steps.
Keywords: chiral pool; dihydroxylation; indolizidines; quinolizidine; ring-closing metathesis